2015
DOI: 10.1080/10408398.2013.809690
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Essential Fatty Acids in Anorexia Nervosa and Obesity

Abstract: The two basic questions in food intake study are what we eat, and how much do we eat. Most research is directed toward the control of how much is eaten. This is likely the result of the increased number of individuals with eating disorders in the Western world. Feeding behavior is highly complex, and is controlled by many psychological, physiological, biochemical, and immunological factors. The aim of this review is to clarify the involvement of fatty acids in eating disorders such as anorexia and binge eating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 156 publications
0
8
0
1
Order By: Relevance
“…It is of high importance to develop improved therapies and preventions for this deadly neurobiological disorder. Polyunsaturated fatty acids exert important biological-, biochemical-, and neuronal mechanisms that are highly relevant to AN including increasing appetite [43], maintaining the integrity and restoring disturbed functions of blood bran barrier [5], stabilizing neuronal membrane fluidity index [44], and mediating cannabinoid signaling and type 1 cannabinoid receptor-mediated functions [45]. With these pivotal role of PUFA in mind, here, we summarized the findings from all studies to date that reported the effectiveness of PUFA supplementation in AN (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of high importance to develop improved therapies and preventions for this deadly neurobiological disorder. Polyunsaturated fatty acids exert important biological-, biochemical-, and neuronal mechanisms that are highly relevant to AN including increasing appetite [43], maintaining the integrity and restoring disturbed functions of blood bran barrier [5], stabilizing neuronal membrane fluidity index [44], and mediating cannabinoid signaling and type 1 cannabinoid receptor-mediated functions [45]. With these pivotal role of PUFA in mind, here, we summarized the findings from all studies to date that reported the effectiveness of PUFA supplementation in AN (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…While PUFAs serve a magnitude of important functions in human biology, the pertinent functions relevant to AN are their beneficial effects on the brain, body weight, and inflammation. Yehuda et al reviewed the importance of PUFA in regulating the activity of blood brain barrier (BBB) and the consequences of PUFA deficiency [44]. Fatty acids occupy 50% of neuronal membrane and 70% of the myelin sheath, which protects and insulates axons to conduct electrical impulses [5].…”
Section: Discussionmentioning
confidence: 99%
“…They found that expression of endogenous cannabinoids acting at brain receptors were reduced in the nucleus accumbens (one of basal ganglia) or another structure in the limbic forebrain and might be involved in the age-dependent decline in food intake. De Boer et al, and Yehuda & Rabinovitz reported that feeding behavior is highly complex, and is controlled by many psychological, physiological, biochemical, and immunological factors [110,111]. Anorexia of aging has a variety of consequences, including a decline in functional status, impaired muscle function, decreased bone mass, micronutrient deficiencies, reduced cognitive functions, increased hospital admission and even premature death, diseases and age-related changes.…”
Section: Age-dependent Decline In the Food Appetite (Anorexia)mentioning
confidence: 99%
“…Basic research has suggested that these agents could increase survival in animal studies [186], and small case reports from one group indicated potentially beneficial effects in AN [187, 188]. Some have made a compelling theoretical argument that this class of nutritional supplements could support brain health in disordered eating [189], but rigorous studies supporting this hypothesis are still outstanding.…”
Section: New Approaches To Medication Intervention In Anmentioning
confidence: 99%